The Caribbean : From Vulnerability to Sustained Growth - Robinson, David (International Monetary Fund, 2006)
This book sets out the economic challenges facing the island nations of the Caribbean and presents policy options to ameliorate external shocks and embark firmly on a sustained growth path. While the countries of the Eastern Caribbean Currency Union that are the focus of the book have enjoyed a sustained period of price and exchange rate stability, they have been buffeted in recent years by adverse shocks, including the erosion of trade preferences, declines in official foreign assistance, and frequent natural disasters. Strengthening their growth performance will require design of a multifaceted strategy that integrates the Caribbean with the global economy, facilitates an economic transformation from agriculture to tourism, fosters greater regional cooperation, and preserves macroeconomic stability. This volume examines the critical issues that are part of that process, including fiscal and financial sector policy, management of external flows, trade integration and tourism, macroeconomic cycles and volatility, and the economic implications of natural disasters.